Two Patients with Therapy-Resistant Pemphigus Vulgaris and Severe Underlying Disease Showing Good Response to a New IVIg Preparation - Katharina Hogrefe; Julia K. Winkler; Alexander H. Enk (Dermatology and Therapy)
Abstract Pemphigus vulgaris is a severe and often therapy-resistant bullous autoimmune disease. Standard therapy with steroids often administered together with another immunosuppressant does not respond in all patients or may not be a good therapeutic option in patients with severe underlying diseases. Intravenous immunoglobulins (IVIgs) represent a treatment alternative, often showing a rapid response which allows one to reduce concomitant immunosuppression. Here, we report on two patients with a complex disease history suffering from severe pemphigus vulgaris who received treatment with a new IVIg preparation (Yimmugo®, 2 g per kg body weight every 4 weeks). IVIg preparations differ regarding manufacturing process and show a varying side effect profile. Both of our patients did not experience any side effects from IVIgs and showed a significant improvement of skin and mucosal erosions. More reports on IVIgs are desirable to help in selecting the optimal preparation and dosing regarding tolerability and effectiveness for individual patients.